2011
DOI: 10.1002/pon.1933
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a needs assessment intervention for people with progressive cancer: Impact on clinical assessment, response and service utilisation

Abstract: The NAT: PD-C is an efficient and acceptable strategy for supporting needs-based cancer care that can potentially be incorporated into standard routine care without increasing the burden on care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
2
21
0
1
Order By: Relevance
“…With regards to sample sources, six studies [ 32 , 40 , 45 , 46 , 49 , 61 ] reported no information regarding the recruitment setting, while in the remaining studies patients, and/or caregivers were mainly recruited from outpatient departments ( n = 16), inpatient departments ( n = 11), home/home-based care units ( n = 10), and mixed settings ( n = 7). In terms of cancer sites, 29 studies focused on patients with mixed cancer site and/or their caregivers, 11 studies focused on specific patients with cancer and/or caregivers (3 studies on prostate cancer [ 57 , 69 , 73 ], 5 studies on breast cancer [ 41 , 48 , 58 , 60 , 75 ], and three on lung cancer [ 35 , 42 , 71 ]), while 10 other studies [ 47 , 50 , 51 , 53 , 59 , 64 , 66 , 68 ] reported no information about cancer types. The diagnostic criteria of advanced cancer were presented in 13 studies (13/50), with five studies [ 6 , 30 , 31 , 60 , 61 ] adopting the criteria of cancer with metastasis, and seven studies [ 9 , 41 , 42 , 45 , 58 , 63 , 75 ] using the stage III/IV criterion according to TNM staging system.…”
Section: Resultsmentioning
confidence: 99%
“…With regards to sample sources, six studies [ 32 , 40 , 45 , 46 , 49 , 61 ] reported no information regarding the recruitment setting, while in the remaining studies patients, and/or caregivers were mainly recruited from outpatient departments ( n = 16), inpatient departments ( n = 11), home/home-based care units ( n = 10), and mixed settings ( n = 7). In terms of cancer sites, 29 studies focused on patients with mixed cancer site and/or their caregivers, 11 studies focused on specific patients with cancer and/or caregivers (3 studies on prostate cancer [ 57 , 69 , 73 ], 5 studies on breast cancer [ 41 , 48 , 58 , 60 , 75 ], and three on lung cancer [ 35 , 42 , 71 ]), while 10 other studies [ 47 , 50 , 51 , 53 , 59 , 64 , 66 , 68 ] reported no information about cancer types. The diagnostic criteria of advanced cancer were presented in 13 studies (13/50), with five studies [ 6 , 30 , 31 , 60 , 61 ] adopting the criteria of cancer with metastasis, and seven studies [ 9 , 41 , 42 , 45 , 58 , 63 , 75 ] using the stage III/IV criterion according to TNM staging system.…”
Section: Resultsmentioning
confidence: 99%
“…They sought a more pragmatic needs assessment to include aspects of physical and social functioning, nutrition and symptom burden to support their self-management and guide their understanding of illness progression. This broader assessment approach has already been successfully employed in time pressured clinics in other settings including cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NAT-C is modelled on an assessment completed by health professionals, the Needs Assessment Tool: Progressive Disease -Cancer, which has been extensively validated and trialed. [11][12][13][14] The NAT-C allows carers to identify and prioritise their own needs, and aims to focus the GP consultation quickly onto relevant matters. The carer and/or patient aimed to book a long appointment and present with a completed NAT-C within a week of the introductory GP interview.…”
Section: Intervention Group Processmentioning
confidence: 99%